Classification and design features of deep washing equipment - Dyachenko, V. (Запоріжжя : ТДАТУ, 2025)
Submersible washing machines are used to clean parts and components of equipment from dirt. Cleaning is carried out by immersing the repair objects in a bath with a solution of synthetic detergents and involves a complex effect on the contamination of physico-chemical and mechanical factors. Physico-chemical effects are carried out by the use of detergents, mechanical effects are carried out by submerged jets of washing liquid.
Keywords: washing machines; cleaning process; rotary activator